Upaya Peningkatan Hasil Belajar Siswa dengan Penerapan Buku Metode Pola dan Rumus Kelas X Keagamaan Madrasah Aliyah Negeri 3 Kota Pekanbaru - Marzuki (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to determine the extent to which the use of patterns and formula method books to improve student learning outcomes of class X Religion MAN 3 Pekanbaru on the topic of polar qiroatul. This research uses action research research method. The population of this study were 24 students of class X Religion with a sample of all students. This research was conducted in 2 cycles. In cycle 1, the pattern and formula method book had not been used, so it was seen that the student learning outcomes were unsatisfactory. Then in cycle 2. the pattern and formula method book was used. It was seen that there was an increase in student learning outcomes, namely as many as 24 students were able to solve the questions correctly and get scores above the KKM. Then the implementation of learning in cycle 2, the steps and planning carried out were the same as cycle 1. The results obtained in cycle 2 were 24 students who were able to complete questions about qiroatul poles and obtained scores above the KKM. From the results of the above research it can be concluded that learning by using pattern and formula method books can improve student learning outcomes in class X Religion. For this reason, it is hoped that the teacher will be able to carry out learning with various models that are in accordance with the characteristics of the learning material.